5M and 7M martensitic stability and associated physical properties in Ni50Mn35In15 alloy: first-principles calculations and experimental verification. (November 2021) - Liang, Xinzeng; Jiang, Xinjun; Gu, Jianglong; Bai, Jing; Guan, Ziqi; Li, Zhenzhuang; Yan, Haile; Zhang, Yudong; Esling, Claude; Zhao, Xiang; Zuo, Liang
Abstract: The excellent magnetic-driven properties of Ni-Mn-based ferromagnetic shape memory alloys are intrinsically related to the presence of the modulated martensite; however, the metastability of modulated martensite hinders the availability of these properties. Herein, the phase stability and associated physical properties of the 5M and 7M modulated martensites in Ni50 Mn35 In15 alloy are studied by the first-principles calculations and experiments. Results show that this alloy undergoes a magneto-structural coupling transformation (i.e., ferromagnetic austenite → ferrimagneitc 5M martensite → ferromagnetic 7M martensite). The stability of the possible phases can be understood based on both the density of states and differential charge densities analysis. A strong bonding ability between Ni and Mn atoms in the 7M martensite is responsible for it being the most stable phase. Graphical Abstract: Image, graphical abstract